Immediate Sequential Bilateral Cataract Surgery: A Systematic Review and Meta-Analysis. (17th August 2015) - Kessel, Line; Andresen, Jens; Erngaard, Ditte; Flesner, Per; Tendal, Britta; Hjortdal, Jesper
Abstract : The aim of the present systematic review was to examine the benefits and harms associated with immediate sequential bilateral cataract surgery (ISBCS) with specific emphasis on the rate of complications, postoperative anisometropia, and subjective visual function in order to formulate evidence-based national Danish guidelines for cataract surgery. A systematic literature review in PubMed, Embase, and Cochrane central databases identified three randomized controlled trials that compared outcome in patients randomized to ISBCS or bilateral cataract surgery on two different dates. Meta-analyses were performed using the Cochrane Review Manager software. The quality of the evidence was assessed using the GRADE method (Grading of Recommendation, Assessment, Development, and Evaluation). We did not find any difference in the risk of complications or visual outcome in patients randomized to ISBCS or surgery on two different dates. The quality of evidence was rated as low to very low. None of the studies reported the prevalence of postoperative anisometropia. In conclusion, we cannot provide evidence-based recommendations on the use of ISBCS due to the lack of high quality evidence. Therefore, the decision to perform ISBCS should be taken after careful discussion between the surgeon and the patient.